A 20-year gap evaluation of the population biology of the crab Hepatus pudibundus in an area overexploited by fisheries - Teles, Jeniffer Natalia [UNESP]; Mantelatto, Fernando Luis; Miazaki, Lizandra Fernandes [UNESP]; Fransozo, Adilson [UNESP]; Bertini, Giovana [UNESP] (Springer Nature, 2020)
The investigation of the temporal dynamics of marine benthonic populations is an important tool to evaluate whether and how they are responding to environmental changes. Here we compared the population biology and reproduction of Hepatus pudibundus in Ubatuba Bay after a 20-year gap. The first samplings were done in September 1995 − August 1996 (hereafter 1ºP), and the second, in September 2016 − August 2017 (hereafter 2ºP). In both periods, five sites were trawled aboard a shrimp fishing boat. We captured 865 crabs in the 1ºP and 4222 in the 2ºP. The mean individual size of each demographic group, the size at the onset of sexual maturity, and the growth rate of females was lower in the 2ºP. The reproductive and recruitment periods were continuous. Our comparable data on population features taken 20-years apart showed adjustments regarding the sizes and abundance of mature individuals of H. pudibundus of Ubatuba Bay, indicating that this species is resilient to the anthropogenic impacts in the region.
Keywords: Brachyura; Flecked box crab; Sex ratio; Sexual maturity; Temporal patterns